2021
DOI: 10.1063/5.0039524
|View full text |Cite
|
Sign up to set email alerts
|

Waiting-time dependent non-equilibrium phase diagram of simple glass- and gel-forming liquids

Abstract: Under numerous circumstances, many soft and hard materials are present in a puzzling wealth of non-equilibrium amorphous states, whose properties are not stationary and depend on preparation. They are often summarized in unconventional “phase diagrams” that exhibit new “phases” and/or “transitions” in which time, however, is an essential variable. This work proposes a solution to the problem of theoretically defining and predicting these non-equilibrium phases and their time-evolving phase diagrams, given the … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 118 publications
0
10
0
Order By: Relevance
“…The present study will be a straightforward extension of the work reported in Refs. [68][69][70][71], which describes the predicted scenario of arrested spinodal decomposition in liquids with excluded-volume plus attractive interactions. The reader is invited to visit these references, which describe in all detail the conceptual and practical challenges found in applying the theory to quenches inside the spinodal re-gion or inside other thermodynamically unstable regions of the state space.…”
Section: The Ne-scgle Theorymentioning
confidence: 99%
See 1 more Smart Citation
“…The present study will be a straightforward extension of the work reported in Refs. [68][69][70][71], which describes the predicted scenario of arrested spinodal decomposition in liquids with excluded-volume plus attractive interactions. The reader is invited to visit these references, which describe in all detail the conceptual and practical challenges found in applying the theory to quenches inside the spinodal re-gion or inside other thermodynamically unstable regions of the state space.…”
Section: The Ne-scgle Theorymentioning
confidence: 99%
“…Therefore, the present study will be based on the NE-SCGLE, a theory that has solidly demonstrated its ability to predict some of the most relevant universal signatures of both, the glass and gel transitions, including aging effects, as well as very specific features reflecting the particular role of the molecular interactions involved in the explicit systems considered so far. For instance, for systems involving only excluded volume interactions, this theory accurately describes the process of formation of high-density hard-sphere-like glasses [2,3,66,67], whereas for liquids with excluded volume plus attractive interactions (i.e., those in vdW's mind) it predicts the formation of sponge-like gels and porous glasses by arrested spinodal decomposition [68][69][70][71]. Extended to multi-component systems [67,72] the NE-SCGLE theory opens the possibility of describing the aging of "double" and "single" glasses in mixtures of neutral [57,73,74] and charged [58,75] particles; the initial steps in this direction are highly encouraging [74].…”
mentioning
confidence: 99%
“…One of the most important challenges in Colloidal Soft Matter Physics is to understand the mechanisms that give rise to the non-equilibrium states of matter. Although there have been important contributions in the particular case of colloidal gels and glasses [27][28][29][92][93][94][95][96][97][98], it has not yet been possible to understand and establish the relationship between these states of matter [28,99], or even more, it is important to explore the possibility of introducing a universal definition of gel [29] and, in addition, it is necessary to quantify the effects that the gravitational field has on the formation of non-equilibrium states [100]. As mentioned above, it is also interesting to study the effective potentials between macromolecules near the gelation or vitrification boundary.…”
Section: Colloidal Soft Matter Out Of Equilibriummentioning
confidence: 99%
“…For example, for simple liquids with purely repulsive interparticle interactions, this theoretical framework accurately describes the non-stationary and non-equilibrium process of the formation of high-density hard-sphere-like glasses, [30][31][32] whereas for liquids with repulsive plus attractive interactions at low densities and temperatures, it predicts the formation of sponge-like gels and porous glasses by arrested spinodal decomposition. [33][34][35][36] The NE-SCGLE was formulated in Ref. 29 and can be summarized in terms of a set of equations that describe the non-equilibrium evolution of the structural and dynamical properties of a simple glass-forming liquid [we refer here for simplicity to a generic system of N identical spherical particles in a volume V that interact through a radially symmetric pair potential U(r)].…”
Section: Introductionmentioning
confidence: 99%